Brain glucose sensing, glucokinase and neural control of metabolism and islet function - Ogunnowo-Bada, E O (Diabetes Obes Metab, 2014)
It is increasingly apparent that the brain plays a central role in metabolic homeostasis, including the maintenance of blood glucose. This is achieved by various efferent pathways from the brain to periphery, which help control hepatic glucose flux and perhaps insulin-stimulated insulin secretion. Also, critically important for the brain given its dependence on a constant supply of glucose as a fuel – emergency counter-regulatory responses are triggered by the brain if blood glucose starts to fall. To exert these control functions, the brain needs to detect rapidly and accurately changes in blood glucose. In this review, we summarize some of the mechanisms postulated to play a role in this and examine the potential role of the low-affinity hexokinase, glucokinase, in the brain as a key part of some of this sensing. We also discuss how these processes may become altered in diabetes and related metabolic diseases.